1998
DOI: 10.3758/bf03330586
|View full text |Cite
|
Sign up to set email alerts
|

Further implications of a computational model of septohippocampal cholinergic modulation in eyeblink conditioning

Abstract: Previously we have shown that Gluck and Myers's (1993) corticohippocampal model could be extended to incorporate Hasselmo and Schnell's (1994) hypothesis that septohippocampal cholinergic processes regulate the amount of information storage in hippocampus. The generalized model could account for the effect of the anticholinergic drug scopolamine in delaying onset of eyeblink conditioning . Here, we show that the model also accounts for additional eyeblink results, including quick recovery after scopolamine is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…Data from animal models of basal forebrain lesion suggest that basal forebrain damage disrupts brain neuromodulatory systems, slowing simple stimulus-response associations, but not necessarily impairing hippocampal-dependent generalization and contextual processing (for review, see Myers et al, 1998). This could account for the current finding that the ACoA group, with basal forebrain damage, was slow to learn a series of stimulus-response associations, but unimpaired on subsequent transfer tests known to be disrupted in individuals with bilateral hippocampal atrophy as well as in the hypoxic group.…”
Section: Discussionmentioning
confidence: 99%
“…Data from animal models of basal forebrain lesion suggest that basal forebrain damage disrupts brain neuromodulatory systems, slowing simple stimulus-response associations, but not necessarily impairing hippocampal-dependent generalization and contextual processing (for review, see Myers et al, 1998). This could account for the current finding that the ACoA group, with basal forebrain damage, was slow to learn a series of stimulus-response associations, but unimpaired on subsequent transfer tests known to be disrupted in individuals with bilateral hippocampal atrophy as well as in the hypoxic group.…”
Section: Discussionmentioning
confidence: 99%
“…The impaired delay conditioning in ACoA amnesia is in accord with prior animal and pharmacological studies suggesting that basal forebrain damage-specifically, medial septal damagedoes disrupt delay eyeblink conditioning. The presumed mechanism of this disruption is that medial septal damage disrupts septohippocampal projections that normally modulate hippocampal processing; hippocampal disruption in turn impairs delay eyeblink conditioning, even though outright hippocampal lesion does not (Myers et al, 1996(Myers et al, , 1998Solomon et al, 1983). In rabbits, medial septal lesions retard the onset of responding (Berry & Thompson, 1979), so that rabbits take longer to start showing CRs.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they suggest that high levels of septohippocampal acetylcholine may increase the rate at which new information is processed and stored by the hippocampus. In subsequent computational modeling, it was shown that this could account for the effects of scopolamine on delay eyeblink conditioning: Specifically, systemic or intraseptal scopolamine slows the onset of delay conditioning but does not affect the rate at which a CR is subsequently acquired nor its eventual asymptotic strength (Myers et al, 1996;Myers, Ermita, Hasselmo, & Gluck, 1998).…”
mentioning
confidence: 99%
“…noted that the role of septal modulation in hippocampal dynamics hypothesized by Hasselmo and colleagues (Hasselmo, 1995;Hasselmo & Schnell, 1994;Hasselmo, Wyble, & Wallenstein, 1996) could be implemented in the Gluck and Myers (1993) corticohippocampal model by assuming that changing the learning rate in the hippocampal system is equivalent to adjusting the amount of time the hippocampus spends storing information. This simple manipulation suffices to account for the effects of septal disruption on the acquisition of a classically conditioned response in humans (Gluck, Allen, & Myers, 2001;Solomon et al, 1993) and other animals (Solomon, Solomon, van der Schaaf, & Perry, 1983) and for the effects of scopolamine on latent inhibition, learned irrelevance, and extinction (Myers, Ermita, Hasselmo, & Gluck, 1998). Hasselmo and Schnell (1994) suggested that although septohippocampal modulation determines what information is stored and recalled in the hippocampus, neurons in the hippocampal system help determine the dynamics of septal modulation.…”
mentioning
confidence: 99%